Transportation of heat and mass of nonlinear mixed convective boundary flow of Casson fluid with generalized Fourier's and Fick's laws and stratification effect. (April 2022) - Saqlain, Muhammad; Anwar, Muhammad Imran; Waqas, Muhammad
The under-consideration article discloses the features of nonlinear mixed convective boundary layer flow of radiative Casson fluid along non-uniform heat source or sink. The generalized Fourier's and Fick's laws and thermophoretic effect are taken to analyze the transportation of heat and mass. The stratification and suction/injection effect are also implemented on the boundary of the sheet. The flow modeled equations are converted into system of coupled nonlinear ODEs by adopting similarity variables. These coupled equations are numerically computed with built-in Bvp4c technique. The developing parameters are described graphically via velocity profile, temperature, and concentration distribution. It is worth revealing that the higher values of the Casson fluid parameter and magnetic field parameter retarded the fluid velocity. It is also noticed that strong temperature is achieved for the higher estimation of non-uniform heat source/sink parameter. Further, enhancement is occurred in the shear stresses, by the enlargement of mixed convection and buoyancy ratio parameter.